1972
DOI: 10.1128/jb.111.1.15-23.1972
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Bacillus subtilis Ribonucleic Acid Polymerase on Deoxyribonucleic Acid from Bacteriophages 2C, φ29, T4, and Lambda

Abstract: Ribonucleic acid (RNA) synthesis primed by bacteriophage T4 or X deoxyribonucleic acid (DNA) with Bacillus subtilis RNA polymerase is severely inhibited by high ionic strength. In contrast, RNA synthesis on B. subtilis bacteriophage 2C, SPOl, or 029 DNA is only moderately affected under similar conditions. The basis of this inhibition lies in the inability of the enzyme to initiate RNA chains with adenosine triphosphate or guanosine triphosphate (ATP, GTP). Binding to templates and the rate of catalysis in hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1974
1974
1979
1979

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 33 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…It has been previously shown that the initiation of 429 RNA synthesis in vitro by B. subtilis RNA polymerase takes place mainly with GTP and to a lesser extent with ATP (26,38). Table 3 also shows that in vitro RNA initiated with [y-32P]GTP (pppG-RNA) hybridized exclusively with the EcoRI-A and -C fragments but not with the EcoRI-B fragment.…”
mentioning
confidence: 81%
“…It has been previously shown that the initiation of 429 RNA synthesis in vitro by B. subtilis RNA polymerase takes place mainly with GTP and to a lesser extent with ATP (26,38). Table 3 also shows that in vitro RNA initiated with [y-32P]GTP (pppG-RNA) hybridized exclusively with the EcoRI-A and -C fragments but not with the EcoRI-B fragment.…”
mentioning
confidence: 81%